The Act of Nusyuz By A Wife As An Abortion of The Right To Maintain Mut'ah After Divorce - Ayu Citra Isnantri; Tanudjaja (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The aim of this research is to understand nusyuz as a reason for divorce in statutory regulations and the judge's considerations in deciding cases of granting mut'ah maintenance to a wife who is suspected of being nusyuz. This research method uses a normative method of analyzing or reviewing court decisions. The subject of the study is law which is conceptualized in a norm or rule that applies in society. Therefore, Normative legal research is focused on the analysis of positive law, principles, doctrine, legal discoveries, legal systematics, comparative or legal history. The results in the Marriage Law and in the Compilation of Islamic Law (KHI) do not specifically emphasize the condition of a wife's nusyuz as a justified reason for divorce, but implicitly this has been represented by 2 (two) other reasons, namely actions that are difficult to change. and constant disputes or quarrels. In this case, nusyuz's attitude certainly needs to receive attention and reprimand from those around him, especially from his partner himself. This is different if it turns out that the reprimand did not produce any results so it should be considered that the perpetrator of nusyuz has found it difficult to change for the better. In other words, such circumstances or conditions should give rise to a dispute between a husband and wife, where the dispute continues to occur over time, it will increasingly erode harmony in the household and be replaced by anger, violence or other harmful things so that it is legally justified to do a divorce.